2022
DOI: 10.6004/jnccn.2021.7115
|View full text |Cite
|
Sign up to set email alerts
|

Four-Year Disease-Free Remission in a Patient With POLE Mutation–Associated Colorectal Cancer Treated Using Anti–PD-1 Therapy

Abstract: The stability of the human genome depends upon a delicate balance between replication by high- and low-fidelity DNA polymerases. Aberrant replication by error-prone polymerases or loss of function of high-fidelity polymerases predisposes to genetic instability and, in turn, cancer. DNA polymerase epsilon (Pol ε) is a high-fidelity, processive polymerase that is responsible for the majority of leading strand synthesis, and mutations in Pol ε have been increasingly associated with various human malignancies. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…A combination of ipilimumab and nivolumab has also been approved for metastatic colorectal cancer with high MSI or mismatch repair defects. Patients with a POLE gene mutation have been reported to benefit from immunotherapy, suggesting that the POLE gene may be a potential marker for CRC treatment (18,19).B.J-C. Rousseau et al (20) reported the first clinical trial to evaluate PD1 in MMR tumors with POLE mutation and found that nivolumab activity appeared in pathogenic mutations of the POLE, such as P286R, V4111L. The POLE mutation site in our case is P286R, which is consistent with the literature, indicating its sensitivity to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of ipilimumab and nivolumab has also been approved for metastatic colorectal cancer with high MSI or mismatch repair defects. Patients with a POLE gene mutation have been reported to benefit from immunotherapy, suggesting that the POLE gene may be a potential marker for CRC treatment (18,19).B.J-C. Rousseau et al (20) reported the first clinical trial to evaluate PD1 in MMR tumors with POLE mutation and found that nivolumab activity appeared in pathogenic mutations of the POLE, such as P286R, V4111L. The POLE mutation site in our case is P286R, which is consistent with the literature, indicating its sensitivity to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Hitherto, limited studies reported the efficacy of immunotherapy for those with POLE mutation in mCRC. Michael recently presented a case who had POLE P286R mutation and was treated with pembrolizumab monotherapy obtaining complete remission and a striking four‐year disease‐free survival 24 . In another study assessing the efficacy of immune treatment in POLE mutations across all tumors, pathogenic POLE mutations, were associated with significant clinical benefits to immunotherapy with DCB reaching 82.4% 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Michael recently presented a case who had POLE P286R mutation and was treated with pembrolizumab monotherapy obtaining complete remission and a striking four‐year disease‐free survival. 24 In another study assessing the efficacy of immune treatment in POLE mutations across all tumors, pathogenic POLE mutations, were associated with significant clinical benefits to immunotherapy with DCB reaching 82.4%. 6 Of three patients with POLE P286R mutation in our study, two received regorafenib and one received capecitabine and bevacizumab as combined regimens when progressed on standard chemotherapy.…”
Section: Discussionmentioning
confidence: 99%